Challenges and opportunities for classroom-based formative assessment and AI: a perspective article - Hopfenbeck, Therese N.; Zhang, Zhonghua; Sun, Sundance Zhihong; Robertson, Pam; McGrane, Joshua A. (Frontiers in Education, 2023)
The integration of artificial intelligence (AI) into educational contexts may give rise to both positive and negative ramifications for teachers' uses of formative assessment within their classrooms.Drawing on our diverse experiences as academics, researchers, psychometricians, teachers, and teacher educators specializing in formative assessment, we examine the pedagogical practices in which teachers provide feedback, facilitate peer-and self-assessments, and support students' learning, and discuss how existing challenges to each of these may be affected by applications of AI.Firstly, we overview the challenges in the practice of formative assessment independently of the influence of AI. Moreover, based on the authors' varied experience in formative assessment, we discuss the opportunities that AI brings to address the challenges in formative assessment as well as the new challenges introduced by the application of AI in formative assessment. Finally, we argue for the ongoing importance of self-regulated learning and a renewed emphasis on critical thinking for more effective implementation of formative assessment in this new AI-driven digital age.